A Case of Bradycardia and Extreme Fatigue. Issue 5 (May 2020) - Kupchik, Nicole; Green, Joel
Abstract : Editor's note: This is the first in a new series on electrocardiography (ECG) interpretation. Nurses in all settings should know the basics, as medications and physiological changes can cause cardiac arrhythmias. Each article will start with a brief case scenario and an ECG strip and then take you step by step through analyzing the heart rhythm. Abstract : This is the first article in a new series on the basics of electrocardiography (ECG) interpretation. After presenting a case scenario and an ECG strip, the authors take readers step by step through analyzing the heart rhythm.